Patient safety and staff psychological safety: A mixed methods study on aspects of teamwork in the operating room - Arad, Dana; Finkelstein, Adi; Rozenblum, Ronen; Magnezi, Racheli (Frontiers in Public Health, 2022)
Objectives: To predict the amount of teamwork that takes place throughout a surgery, based on performing a preoperative safety standards (surgical safety checklist and surgical count) and to explore factors affecting patient safety and staff psychological safety during a surgery, based on interprofessional teamwork. Methods: This mixed methods study included quantitative and qualitative analyses. Quantitative data included 2,184 direct observations of surgical cases with regard to the performance of safety standards during surgeries in 29 hospitals, analyzed using multivariate binary logistic regressions. Qualitative data were obtained from an analysis of 25 semi-structured interviews with operating room (OR) clinicians and risk managers, using an inductive thematic analysis approach. Results: Analysis of the OR observations revealed that a lack of teamwork in the preoperative “sign-in” phase doubled the chances of there being a lack of teamwork during surgery (odds ratio = 1.972, 95% confidence interval (CI) 1.741, 2.233, p<0.001) and during the “time-out” phase (odds ratio = 2.142, 95% CI 1.879, 2.441, p<0.001). Consistent presence of staff during surgery significantly increased teamwork, by 21% for physicians and 24% for nurses (p<0.05), but staff turnover significantly decreased teamwork, by 73% for physicians (p<0.05). Interview data indicated that patient safety and staff psychological safety are related to a perception of a collaborative team role among OR staff, with mutual commitment and effective interprofessional communication. Conclusions: Healthcare organizations should consider the key finding of this study when trying to identify factors that affect teamwork during a surgery. Effective preoperative teamwork positively affects intraoperative teamwork, as does the presence of more clinicians participating in a surgery, with no turnover. Other factors include working in a fixed, designated team, led by a surgeon, which functions with effective interprofessional communication that promotes patient safety and staff psychological safety.